ANALISIS KINERJA KEUANGAN DAN KEPUASAN NASABAH TERHADAP PELAYANAN LEMBAGA KEUANGAN MIKRO AGRIBISNIS (LKM-A) “RUKUN TANI” DI KABUPATEN BOGOR - Putri Kusumaningtyas; Heny Kuswanti Suwarsinah Daryanto (Forum Agribisnis, 2012)
One of agricultural problems that occurred in Indonesia is the lack of capital received by farmers to develop their business. The existence of microfinance institutions agribusiness “Rukun Tani” are expected to be a solution to these problems. Evaluation of  LKM-A“Rukun Tani” is necessary, because LKM-A “Rukun Tani” is the formation of the government’s development program. As we know, many government programs that fail in development. Evaluation is done by looking at performance from two sides, from financial performance and from customer satisfaction. This research, showed that the financial performance of LKM-A “Rukun Tani” showed a very good condition. Indicated by the ratio which is above the minimum standard. And for customer satisfaction, is measured by using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Based on the measurements, showed that the respondents expressed satisfaction with the performance of LKM-A “Rukun Tani”.